Regulation of CaV1.2 Current: Interaction With Intracellular Molecules - Takeshi Kobayashi; Yoichi Yamada; Mitsuhiro Fukao; Masaaki Tsutsuura; Noritsugu Tohse (Elsevier, 2007)
CaV1.2 (α1c) is a pore-forming subunit of the voltage-dependent L-type calcium channel and is expressed in many tissues. The β and α2/δ subunits are auxiliary subunits that affect the kinetics and the expression of CaV1.2. In addition to the β and α2/δ subunits, several molecules have been reported to be involved in the regulation of CaV1.2 current. Calmodulin, CaBP1 (calcium-binding protein-1), CaMKII (calcium/calmodulin-dependent protein kinase II), AKAPs (A-kinase anchoring proteins), phosphatases, Caveolin-3, β2-adrenergic receptor, PDZ domain proteins, sorcin, SNARE proteins, synaptotagmin, CSN5, RGK family, and AHNAK1 have all been reported to interact with CaV1.2 and the β subunit. This review focuses on the effect of these molecules on CaV1.2 current. Keywords:: CaV1.2, calcium, channel, current